Regulation of Innate Lymphoid Cells by Aryl Hydrocarbon Receptor - Li, Shiyang; Bostick, John W.; Zhou, Liang (Frontiers in Immunology, 2018)
With striking similarity to their adaptive T helper cell counterparts, innate lymphoid cells (ILCs) represent an emerging family of cell types that express signature transcription factors, including T-bet+ Eomes+ natural killer (NK) cells, T-bet+ Eomes– group 1 ILCs (ILC1), GATA3+ group 2 ILCs (ILC2), RORγt+ group 3 ILCs (ILC3), and newly identified Id3+ regulatory ILC (ILCreg). ILCs are abundantly present in barrier tissues of the host (e.g., the lung, gut, and skin) at the interface of host-environment interactions. Active research has been conducted to elucidate molecular mechanisms underlying the development and function of ILCs. The aryl hydrocarbon receptor (Ahr) is a ligand-dependent transcription factor, best known to mediate the effects of xenobiotic environmental toxins and endogenous microbial and dietary metabolites. Here we review recent progresses regarding Ahr function in innate lymphoid cells. We focus on the Ahr-mediated cross-talk between ILCs and other immune/non-immune cells in host tissues especially in the gut. We discuss the molecular mechanisms of the action of Ahr expression and activity in regulation of ILCs in immunity and inflammation, and the interaction between Ahr and other pathways/transcription factors in ILC development and function with their implication in disease.